Semiotic: Analysis of Verbal and Nonverbal Signs of Canggu Weekly Advertisement - Suryani, Ni Wayan; Suastini, Ni Wayan (Humanis; Vol 27 No 2 (2023)DO - 10.24843/JH.2023.v27.i02.p03, 2023)
An advertisement is a form of communication used to persuade an audience (viewers, readers, or listeners) to take some action concerning the product, the ideas, or the service. This study focuses on a single advertisement; The Canggu weekly advertisement Strongly conveys promotion Using verbal and nonverbal signs. The study Determined to find out the verbal and nonverbal signs in used in the advertisement and their meaning. The study uses a qualitative descriptive method and two theories in analysing the data. The first was the theory of Semiotic by Saussure (1893), and the theory of meaning by Barthes (1977). The findings show that the signs in this advertisement typically have a literal or denotative meaning in explaining the product. The same thing in the nonverbal signs the dominant meaning used was denotative meaning. It is because the literal meaning is making the reader easier to catch the message delivered by a print advertisement or an online advertisement.